PERBAIKAN PENGOLAHAN PRODUK DARI ALPUKAT - Anis, Ulfah; Intara, Yazid Ismi; Elvina, Wica (Jurnal Abdi Insani, 2025)
The Women’s Environmental Conservation Cooperatives (Koperasi Perempuan Pelestari Lingkungan, or KPPL) Sumber Jaya and KPPL Sejahtera in Sumber Bening Village, Rejang Lebong Regency, have been producing avocado jam. However, the jam's consistency has lacked uniformity, primarily due to the absence of pectin or gelatin, which affects texture. This community service activity aims to enhance the target audience's knowledge and skills in improving the avocado jam production process. The methods used included coordination, counseling, and hands-on practice, conducted in Sumber Bening Village. The activity provided counseling on avocado quality, raw materials, and the processing techniques for making avocado jam. Additionally, the service team demonstrated the avocado jam-making process in front of the target audience. The activity participants were given knowledge about pectin and gelatin, which play a role in influencing the texture of products. Pectin and gelatin come from different raw materials. Pectin is usually derived from citrus peels, while gelatin comes from fish scales and fish bones. The participants also had the opportunity to make avocado jam with the addition of pectin and gelatin. This community service activity demonstrated the participants' enthusiasm in making avocado jam, which was carried out through lectures and practical sessions.